The Effect of Education and Work Achievement on the Career Development of Employees With Work Motivation as a Mediator at the West Sumatra Regional Financial and Asset Management Agency Office - Susanti, Febsri; Afifah, Pritania (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the effect of education and work performance on the career development of employees with work motivation as a mediator at the office of the financial and asset management agency in the West Sumatra region. Respondents in this study were 70 people with the Total Sampling technique. Analysis of the data used is multiple linear regression. The test results show that education has a positive and significant effect on employee career development. Work performance has a positive and significant effect on employee career development. Education has a positive and significant effect on work motivation. Work performance has a positive and significant effect on work motivation. Work motivation has a positive and significant effect on employee career development. Education has a positive and significant effect on employee career development through work motivation. And work performance has a positive and significant effect on employee career development through work motivation